Effectiveness of physical exercise on mental health among university students: a systematic review and meta-analysis - Liu, Longyan; Xin, Xianyang; Wang, Hai; Zhang, Ying (Frontiers in Psychology, 2025)
IntroductionThe global incidence of adverse mental health symptoms among university students at various stages has been increasing year by year. Compared to passive medical treatments, physical exercise, as a rehabilitative therapeutic approach, appears to play a significant role in preventing poor mental health among students. This meta-analysis aims to evaluate the impact of physical activity interventions on the mental health status of university students.MethodThis study systematically searched PubMed, Cochrane Library, Web of Science, Embase, and Scopus for randomized controlled trials (RCTs) from the inception of the databases up to March 2025. The study participants were university students, and the outcome measures included mental health indicators such as wellbeing, anxiety, depression, stress, and sleep quality. Meta-analysis of the included studies was conducted using Review Manager 5.4 and Stata 16 software.ResultsA total of 34 articles comprising 80 individual studies and 8,020 participants were included in the meta-analysis. Physical activity interventions were significantly associated with improvements in university students’ mental health outcomes. Specifically, exercise demonstrated a large positive effect on overall mental health (SMD = 0.91, 95% CI: 0.15 to 1.67), enhanced wellbeing (SMD = 0.41, 95% CI: 0.29 to 0.53), and led to moderate reductions in anxiety (SMD = −0.62, 95% CI: −0.84 to −0.41), depression (SMD = −0.67, 95% CI: −0.91 to −0.43), and stress (SMD = −0.46, 95% CI: −0.64 to −0.28). Sleep quality also improved significantly (SMD = −0.57, 95% CI: −0.74 to −0.40). Subgroup analyses indicated that interventions with a lower frequency (≤3 sessions per week) and longer duration (10–48 weeks) were particularly effective. Among exercise types, resistance training and high-intensity interval training showed the strongest effects on anxiety, depression, and stress reduction, while aerobic exercise was most effective for improving sleep quality.ConclusionActive participation in physical exercise has been shown to significantly improve the mental health of university students. To further enhance students’ psychological wellbeing and prevent mental health disorders, it is crucial to promote regular physical activity. Engaging in regular exercise can help alleviate symptoms of depression, anxiety, and stress, while also improving overall wellbeing and sleep quality.Systematic review registrationPROSPERO registration: CRD420251016260; publicly accessible at: https://www.crd.york.ac.uk/prospero/.